Write your own mystery story - Farrell, Tish. (Minneapolis, MN : Compass Point Books, 2006)
A brief guide to writing mystery stories teaching how to craft characters and plots, set the scene, use dialogue, and build suspense.
Getting started -- Setting the scene -- Characters -- Viewpoint -- Synopses and plot -- Winning words -- Scintillating speech -- Hints and tips -- The next step -- Find out more.
Includes bibliographical references (p. 62) and index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
6.5
5-8
Keywords: Detective and mystery stories -- Authorship -- Juvenile literature; Mystery and detective stories -- Authorship; Mystery fiction -- Technique